Photodynamic inactivation in the expression of the Candida albicans genes ALS3, HWP1, BCR1, TEC1, CPH1, and EFG1 in biofilms - Freire, Fernanda [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Pereira, Cristiane Aparecida [UNESP]; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Springer Nature, 2018)
The objective of this study was to evaluate the effects of photodynamic inactivation (PDI) on Candida albicans biofilms, evaluating its effects on gene expression of ALS3, HWP1, BCR1, TEC1, CPH1, and EFG1 by yeast. Three samples of C. albicans were used in this study: a clinical sample from a patient with HIV (39S), a clinical sample from a patient with denture stomatitis lesion (Ca30), and a standard strain ATCC 18804. The quantification of gene expression was related to the production of those genes in the samples referred above using quantitative polymerase chain reaction (qPCR) assay in real time. The photosensitizer methylene blue at 300 uM and erythrosine at 400 uM, sensitized with low-power laser (visible red, 660 nm) and green LED (532 nm), respectively, were used for PDI. Four groups of each sample and PDI protocol were evaluated: (a) P+L+: sensitization with the photosensitizer and irradiation with light, (b) P+L−: only treatment with the photosensitizer, (c) P−L+: only irradiation with light, and (d) P−L−: without sensitization with the dye and absence of light. The results were analyzed by t test, with a significance level of 5%. The photodynamic inactivation was able to reduce the expression of all genes for both treatments, laser and LED. The fold-decrease for the genes ALS3, HWP1, BCR1, TEC1, CPH1, and EFG1 were 0.73, 0.39, 0.77, 0.71, 0.67, and 0.60 for laser, respectively, and 0.66, 0.61,.050, 0.43, 0.54, and 0.66 for LED, respectively. It could be concluded that PDI showed a reduction in the expression of C. albicans genes, suggesting its virulence decrease.
Keywords: Biofilms; Candida albicans; Photodynamic inactivation; Real-time PCR; Virulence factors